Peningkatan Motivasi Kerja Guru Ditinjau Dari Kepemimpinan Kepala Sekolah - Daud Daud; Kun Nurachadijat (Simpati, 2023)
To find out the influence of the principal's leadership, work motivation, and other factors, research has been conducted. In this study analyzed various factors that affect teacher performance MTs Al Marwah Pameungpek Bandung. Researcher explored the influence of the principal's leadership on teacher performance motivation at the Mts Al Marwah School. The sample size consisted of 38 teachers as teaching staff, during the research month of May - June 2023. Our research approach is descriptive qualitative. Our data analysis yielded some interesting results with a fairly good contribution, found a significant and affirmative correlation between the principal's leadership on teacher performance motivation. In addition, this study reports a significant and optimistic correlation between principal leadership and teacher performance motivation. In addition, there is a noteworthy and beneficial relationship between work motivation and teacher performance motivation and effective contribution. This research concludes that the effect of teaching and learning processes on achieving the school's vision through the Principal's Leadership on Teacher Performance Motivation at the Mts Al Marwah School